2019
DOI: 10.1186/s13048-019-0592-3
|View full text |Cite
|
Sign up to set email alerts
|

S100A10 silencing suppresses proliferation, migration and invasion of ovarian cancer cells and enhances sensitivity to carboplatin

Abstract: BackgroundOvarian cancer is the leading cause of gynecological cancer-related mortality. The novel oncogene S100A10 has been reported to be involved in cancer cell proliferation, invasion and metastasis. The role of S100A10 in ovarian cancer has not been well studied and the effect of S100A10 on chemotherapy remains unclear. The aims of the present study were to investigate the functional role of S100A10 in the progression and carboplatin sensitivity of ovarian cancer.MethodsWe examined the expression levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Additionally, S100A10 also regulated the metastasis of lung cancer cells by the interaction with DLC1 (Yang et al, 2011). Recently, Cui's group reported that S100A10 was an oncogene in ovarian cancer by promoting tumor metastasis, and reduced sensitivity to carboplatin (Wang et al, 2019b). In our study, we found that S100A10 promoted the migration and invasion of Hep3B cells.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Additionally, S100A10 also regulated the metastasis of lung cancer cells by the interaction with DLC1 (Yang et al, 2011). Recently, Cui's group reported that S100A10 was an oncogene in ovarian cancer by promoting tumor metastasis, and reduced sensitivity to carboplatin (Wang et al, 2019b). In our study, we found that S100A10 promoted the migration and invasion of Hep3B cells.…”
Section: Discussionsupporting
confidence: 69%
“…The abnormal expression of S100A10 affects cell proliferation, apoptosis, angiogenesis, inflammation, and invasion. Numerous studies have confirmed that S100A10 is an oncogene, such as intestinal cancer (Suzuki et al, 2011), basal-type breast cancer (McKiernan et al, 2011), lung cancer (Katono et al, 2016), ovarian cancer (Wang et al, 2019b), pancreatic ductal cancer (Bydoun et al, 2018), and gastric cancer (El-Rifai et al, 2002). S100A10 has also been noted in HCC (Kittaka et al, 2008;Shan et al, 2013;Zhang et al, 2016;Lou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that upregulation of S100A10 was characteristically observed in the CD44 + breast cancer cells but not in CD44breast cancer cells among the metastasized cells in the liver ( Figure 1C) further supports a notion that S100A10 has specific roles in the regulation of the metastasis of breast cancer CSCs in vivo. Although S100A10 promotes multiple oncogenic properties including proliferation, invasion, and migration especially in ovarian cancers, 38,39 the effect of S100A10 on proliferation and migration was not evident in breast cancer cells and PDX cells, suggesting that the effect of S100A10 on oncogenic properties is cell type-dependent ( Figure S2-S6).…”
Section: Discussionmentioning
confidence: 99%
“…For example, loss of p11 in ovarian cancer cells resulted in reduced tumor growth in NOD/SCID mice In Vivo with concurrent reduction of cell proliferation, colony formation, migration, and invasion In Vitro. Moreover, p11-depleted cells show decreased resistance to carboplatin In Vitro [209]. Li Y et al, recently demonstrated the importance of p11 in gastric cancer tumorigenesis.…”
Section: Involvement Of P11 In Biological Processes and Cancermentioning
confidence: 99%